SALES MARKETING STRATEGY IN THE PETISAH MARKET DURING COVID 19 - Suhairi; Amelia Padillah Siregar; Bunga Mawar; Mela Devita; Taufik Hidayat (Journal of Social Research, 2022)
This study aims to determine the Marketing Strategy of MSME Sales in the Petisah Market during the Covid 19 Period. The research methodology used is a qualitative qualitative research approach, which is research that presents and data based on the results of documentation that can provide a clear picture of the object being studied, for later analysis. process and analyzed to then draw conclusions. The data analysis method used is qualitative where the data used in the study describes an object or phenomenon based on things that generally cannot be calculated using documentation data, literature studies, and secondary data. With the development of the business world today, MSMEs are required to pay more attention to competition in the business world, both domestically and abroad. If MSMEs want to remain competitive with other companies, MSMEs must pay attention to the main problem, namely marketing. Effective Product Marketing Strategies During the Covid-19 Pandemic Period, namely: offering services or products to customers who need assistance, using the right tools, maximizing old features or new features that suit the needs of the community or customers, avoiding all negative impressions can ruin your business